Profitability Ratio Determinants on PT. Bank BRI Tbk Period 2011- 2021 - Muliahadi Tumanggor (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to discuss the effect of CAR, NPL dan SBI on ROA. The research methods used in this study are quantitative descriptive research as well as using statistical analysis. The population used is the financial statements of PT. Bank BRI Tbk. The sample used is data derived from records of financial statements and income statements for the period 2011 to 2021. Data collection techniques use classical assumption test techniques that include normaliity test, heteroskedasticities test, multicollinearities test, and autocorrelations test. In addition, multiple linear regression analysis techniques are also carried out, hypothesis tests (t tests), simultaneous tests (F tests), correlation coefficient tests, and determination coefficient tests with the SPSS 24 application program. The results of this study indicate that NPL, SBI has a significant effect on ROA. While CAR does not have a significant effect on.